HUBUNGAN KENAIKKAN BERAT BADAN SELAMA HAMIL DENGAN KEJADIAN BERAT BAYI LAHIR RENDAH (BBLR) DI RSUD SETJONEGORO KABUPATEN WONOSOBO TAHUN 2010 - Galuh, Elok; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
One of the indicators to determine the degree of public health is the Infant Mortality Rate (IMR). IMR in Central Java province in 2008 of  9.17 per 1000 births. Largest cause of infant deaths is due to perinatal disorders. Of all perinatal deaths of about 2-27% due to the birth of Low Birth Weight Infants (LBW) due to malnutrition or poor nutrition. Knowing the relationship of weight gain during pregnancy with the incidence of Low Birth Weight Infants  (LBW)  in Wonosobo regency Setjonegoro Hospital. This type of research was analytic correlation by used case control. Sampling technique used purposive sampling, and the sample size in this study were 94 people with 47 respondents LBW as the case group and 47 infants reponen normal control group. Bivariate analysis used the spearman rank. The increases in maternal weight during pregnancy in hospitals Setjonegoro most normal mothers of 49 respondents  (52.1%).  Babies born with  normal weight and LBW a number of  47 events (50%). Based on bivariate  tests  used spearman rank analysis found that the phi value 0.000. p value  < 0.05.  It  showed a significant relationship between weight gain during pregnancy increase the incidence of LBW in hospitals Setjonegoro Wonosobo. There is a rise in weight gain during pregnancy with the incidence of LBW in hospitals Setjonegoro Wonosobo. Pregnant women need to add information about the increase of normal weight with doing routine ANC to anticipate the occurrence of LBW.   Key words: weight gain during pregnancy, the incidence of LBW